An Oxalate‐Bridged Binuclear Iron(III) Ionic Liquid for the Highly Efficient Glycolysis of Polyethylene Terephthalate under Microwave Irradiation. Issue 7 (2nd May 2019) - Cot, Sergi; Leu, Meike K.; Kalamiotis, Alexis; Dimitrakis, Georgios; Sans, Victor; de Pedro, Imanol; Cano, Israel
Abstract: An oxalate‐bridged binuclear iron(III) ionic liquid combined with an imidazolium based cation, (dimim)2 [Fe2 Cl4 (μ‐ox)], was synthesized and characterized by a wide range of techniques. This halometallate ionic liquid was active in catalyzing the depolymerization of polyethylene terephthalate (PET) by glycolysis, under conventional and microwave‐assisted heating conditions. Both methodologies were very selective towards the production of bis(2‐hydroxyethyl)terephthalate (BHET). The employment of microwave heating proved beneficial in terms of time and energy saving when compared to the use of thermal heating. Indeed, dielectric spectroscopy studies revealed that the binuclear iron‐containing ionic liquid exhibits an excellent heating response under an electromagnetic field. The catalyst provided quantitative conversions to BHET in the glycolysis of post‐consumer PET bottles in only 3 h through microwave heating, as compared to 80 % conversion after 24 h under conventional heating. Abstract : Auf wiedersehen, PET : An ionic liquid based on an imidazolium cation and an iron oxalate anion induces the efficient glycolysis of polyethylene terephthalate (PET) under microwave and thermal heating conditions. The dielectric properties of the catalyst lead to a considerable reduction in reaction time when microwave irradiation is employed. This work provides valuable insights for the development of highly active, stable and recyclable catalysts for the efficient depolymerization of PET into highly pure monomers.